Social and Emotional Interactions for AI - Davtyan, Mariam A. (Տիգրան Մեծ)
Advancements in artificial intelligence (AI) and robotics are ushering in systems capable of mean-ingful, human- like interactions. This article explores the integration of large language models (LLMs) into humanoid robots, also emphasizing the existence of technologies allowing robots to mimic human sensory systems—vision, hearing, touch, and smell—and analyze stimuli to generate emotionally resonant responses. A central focus is placed on the role of communication in fostering empathy. Drawing on philosophical insights and technological innovations, we propose that AI systems can enhance their intellectual and emotional capabilities through experiential learning. Embedding robots in “social schools” or “kindergartens,” where they observe and practice body language, cultural norms, and emotional expressions, is suggested as a pathway to developing empathy and understanding. This approach is not just about programming intelligence but nurturing it, ensuring these systems embody human- like emotional depth and cultural awareness. By fostering communication-driven development, AI can evolve into companions capable of meaningful, empathetic relationships, advancing human-machine integration while maintaining ethical considerations.
Keywords: Human-AI interaction